Delusions and Responsibility for Action: Insights from the Breivik Case - Bortolotti, L; Broome, M; Mameli, M (Springer Netherlands, 2014)
What factors should be taken into account when attributing criminal responsibility to perpetrators of severe crimes? We discuss the Breivik case, and the considerations which led to holding Breivik accountable for his criminal acts. We put some pressure on the view that experiencing certain psychiatric symptoms or receiving a certain psychiatric diagnosis is sufficient to establish criminal insanity. We also argue that the presence of delusional beliefs, often regarded as a key factor in determining responsibility, is neither necessary nor sufficient for criminal insanity. © 2013 The Author(s).